The Effect of Single Leg Hop Exercise on Leg Muscle Power in Men's Low Kick Right Low Kick Wushu Sanda Athletes, Kediri City in 2022 - Thasania Charla; Mokhammad Firdaus; M. Akbar Husein Alsabbah (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2023)
The discovery of problems, not all of them are used as problems in this study, therefore from the problem "The Effect of Single Leg Hop Exercise on Leg Muscle Power in Men's Low Kick Right Low Kick Wushu Sanda Athletes, Kediri City in 2022. Quantitative research So the population in this study were 16 athletes, so the researchers took a total sampling technique to collect a sample of 16 athletes. The leg muscle power components include: vertical jump test. From the results of statistical calculations, the value of the t test, normality, homogeneity is 0.000 <0.05. The normality of the sig value for the experimental group's pretest was 276, the control group's pretest was 189, the experimental group's posttest was 375, the control group's posttest was 080 > 0.05. And homogeneity was obtained sig for the experimental pretest group of 078, the control group's pretest was 189, the experimental group's posttest was 313, and the control group's posttest was 080 > 0.05. So it can be concluded that there is an effect of giving single leg hop training on leg muscle power in the low right low kick male wushu sanda athletes in Kediri City 2022.